'Strandentwining cable' Joyce, Flaubert, and intertextuality - Baron, Scarlett, 1982- (Oxford : Oxford University Press, 2012)
Baron explores the works of two of the most admired and mythologized masters of 19th- and 20th-century prose: Gustave Flaubert (1822-1880) and James Joyce (1882-1941). She uncovers the lifelong fascination that Joyce harboured for Flaubert and investigates how this heightened interest inflected his own creative practice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Joyce, James, -- 1882-1941 -- Criticism and interpretation; Flaubert, Gustave, -- 1821-1880 -- Criticism and interpretation; Flaubert, Gustave, -- 1821-1880 -- Influence; Intertextuality